Analisis Pengaruh IPO Terhadap Kinerja Keuangan Dan Nilai Perusahaan Pada Sektor Teknologi Di BEI - Muhammad Ramdani; M. Adrian; Nuraisyah Usyshifa Ramadhani; Holijah Holijah (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of Initial Public Offerings (IPOs) on the financial performance and value of companies in the technology sector listed on the Indonesia Stock Exchange (IDX). The main problem in this study is the inconsistency of previous research findings regarding the impact of IPOs, particularly on technology companies characterized by high growth but unstable profitability. The method used is library research with a descriptive qualitative approach, through the collection and analysis of various scientific literature in the form of relevant national and international journals for the period 2020–2026. The results show that IPOs increase liquidity and improve a company's capital structure, but this does not always translate into increased profitability in the short term. Furthermore, IPOs also have a positive impact on company value, driven by investor expectations and increased transparency and corporate governance. Thus, IPOs are an important strategy that provides long-term benefits, although they require optimal management to sustainably improve financial performance.